Gender differences in self-reported social functioning of patients with chronic coronary artery disease and affective disorders - E. V. Lebedeva; E. D. Schastnyy; T. G. Nonka; A. N. Repin (Бюллетень сибирской медицины, 2021)
Aim. To determine gender differences in self-reported social functioning of patients with comorbidity of affective disorders (ADs) and chronic coronary artery disease.Materials and methods. Self-reported social functioning of 248 cardiological patients (194 men (78.2%) and 54 women (21.8%)) with chronic coronary artery disease (CAD) and ADs was studied using the Social Adaptation Self-evaluation Scale (SASS). The mean age of patients with chronic CAD in men was (57.2 ± 6.5) years, and in women (59.3 ± 7.1), p = 0.04. Qualitative and quantitative indicators were investigated using the Mann – Whitney, Wilcoxon and T-test; χ2 (Pearson›s goodness-of-fit test) was used to estimate the frequencies.Results. ADs were represented by chronic mood disorders (45%), first-time depressive episodes (DEs) 24%, recurrent DEs 24.5%, as well as bipolar II disorder (BD II) 6.5%. ADs in 42.4% of patients were associated with psychosocial stressors (mainly, loss), p = 0.02. Men statistically significantly  more often (37.1%, 72/194) than women (16.7%, 9/54) communicated more scarcely with others as a result of projection mechanisms, a high level of hostility, passive aggressiveness and lack of initiative, typical for patients with ADs, p = 0.003.Conclusion. The social functioning of patients with ADs and chronic coronary artery disease was complicated irrespective of gender. Women were single and bereaved of their children more often than men. Due to the low level of communication outside the family and outside of professional activity, most of the patients maintained communication mainly with the family. However, due to ADs, they were not able to feel support from familymembers and rarely initiated communication with other people (men did it statistically significantly more often than women).